2016
DOI: 10.1073/pnas.1614688113
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regions that control ion selectivity and calcium-dependent activation in the bestrophin ion channel

Abstract: Cytoplasmic calcium (Ca 2+ ) activates the bestrophin anion channel, allowing chloride ions to flow down their electrochemical gradient. Mutations in bestrophin 1 (BEST1) cause macular degenerative disorders. Previously, we determined an X-ray structure of chicken BEST1 that revealed the architecture of the channel. Here, we present electrophysiological studies of purified wild-type and mutant BEST1 channels and an X-ray structure of a Ca 2+ -independent mutant. From these experiments, we identify regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
135
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(152 citation statements)
references
References 43 publications
15
135
2
Order By: Relevance
“…The importance of these is exemplified by the fact that the I205T BEST1 mutation has been reported to cause retinitis pigmentosa (Davidson et al, 2009). Recent electrophysiological studies performed by Vaisey et al have revealed specific regions that control both ion selectivity and calcium activation (Vaisey et al, 2016). Their experiments strongly demonstrate that the neck does not significantly affect ion selectivity but instead primarily serves to act as a gate to calcium-dependently control chloride permeation.…”
Section: Best1 Protein Structure and Topologymentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of these is exemplified by the fact that the I205T BEST1 mutation has been reported to cause retinitis pigmentosa (Davidson et al, 2009). Recent electrophysiological studies performed by Vaisey et al have revealed specific regions that control both ion selectivity and calcium activation (Vaisey et al, 2016). Their experiments strongly demonstrate that the neck does not significantly affect ion selectivity but instead primarily serves to act as a gate to calcium-dependently control chloride permeation.…”
Section: Best1 Protein Structure and Topologymentioning
confidence: 99%
“…Their experiments strongly demonstrate that the neck does not significantly affect ion selectivity but instead primarily serves to act as a gate to calcium-dependently control chloride permeation. Moreover, they find that the cytosolic aperture of the pore controls the relative permeability of the channel to different anions (Vaisey et al, 2016). …”
Section: Best1 Protein Structure and Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…5) 22,23 . Intriguingly, the animal Bestrophin channel, whose narrow pathway is formed by three layers of Ile, Phe, and Phe, is an anion selective channel while the bacterial Bestrophin, which contains Ile, Ile, and Phe at the bottle neck, has been shown to be cation selective channel 22,24,25 .…”
mentioning
confidence: 99%
“…It is bound by eight water molecules in an anti-prismatic geometry ( fig. S8), which are in turn coordinated by backbone oxygens of Leu 42 , Ser 43 and Ser 44 (Fig. 2B).…”
mentioning
confidence: 99%